Language beyond the classroom a guide to community-based learning for world language programs - Purdy, Jann (Cambridge Scholars Publishing, 2018)
"Language Beyond the Classroom is an edited volume of essays that offers detailed, how-to guides for developing, implementing, and evaluating service-learning programs for a variety of languages. Contributions here present civic-engagement programs for several languages, including French, German, Russian, and Spanish, with curricula that can be adapted to any language program. The authors of each essay engage with the growing pedagogical emphasis on experiential learning, providing theoretical and practical advice, including syllabi, for language educators. Language Beyond the Classroom is a timely exploration of the variety and richness of service-learning in language instruction, and contributes to a 21st-century emphasis on community engagement and cultural contextualization in second-language pedagogy" -- From back cover.